Sense and Nonsense: The Literary Significance of Semantic Contradictions and Tautology in Okot p’Bitek’s Song of Lawino - Ofuani, Ogo (Meta, 1990)
AbstractA knowledge of the collocational principles governing the cooccurrence of words aids the linguistic analyses of eccentric poetic usages such as oxymoron, paradox, and tuatology. These forms can be more formally linguistically analysed and insights gained complement the literary critic's efforts. This paper shows how these semantically deviant constructions contribute to "meaning" in Okot p'Bitek's Song of Lawino. Lawino exploited them for satire. Tautology is vacuous, empty, meaningless; but she used it to communicate her disgust and dissatisfaction at her husband's unsociable behaviour. Her use of oxymoron and paradox is linked to her tendency to exaggerate; but these exaggerations are to shock her erring husband to realization. He had shriked his marital and parental responsabilities and needed to be reminded. Their literary significance hinge on their situational meaningfulness. The critic must develop the ability to understand, explain and interpret such usages; and thus make literary sense of semantic nonsense.